2021
DOI: 10.1088/1742-6596/1968/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of student difficulties in learning refraction of light

Abstract: The use of semiotic resources in developing abilities and skills in physics problems is very important. PIMCA learning model (Presentation, Idea Mapping, Conceptualization and Formative Assessment) introduced and developed by Cosmas Poluakan is the focus of this research. The purpose of this study was to analyze student difficulties on learning the refraction using the PIMCA model based on multi-representation (MR). The type of research used experimental research with one group pretest-posttest design. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Physics material that students consider difficult includes light waves (Kaltakci-Gurel et al, 2016;Nasir et al, 2021). Based on research by Dido et al (2021), it can be concluded that students still have problems understanding light refraction, such as drawing the angle of incidence, direction of refraction, and position of refraction for two different media. Another difficulty that is often encountered is that students only tend to use a geometric optical approach in analyzing light wave phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Physics material that students consider difficult includes light waves (Kaltakci-Gurel et al, 2016;Nasir et al, 2021). Based on research by Dido et al (2021), it can be concluded that students still have problems understanding light refraction, such as drawing the angle of incidence, direction of refraction, and position of refraction for two different media. Another difficulty that is often encountered is that students only tend to use a geometric optical approach in analyzing light wave phenomena.…”
Section: Introductionmentioning
confidence: 99%